The Future of Ageing in Europe Making an Asset of Longevity - Walker, Alan (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book provides the most comprehensive analysis available of the challenges created by Europe's ageing population. Grounded in state-of-the-art scientific assessments by leading European researchers, the book is strongly policy focused. Indeed this book contains a detailed account of the policies required across a broad field, from economic sustainability and extending working lives, to healthy ageing, technological innovation, long term care and political citizenship, for the successful adaptation to the challenges of ageing in Europe and globally. It is a policy manifesto to ensure that the future of ageing in Europe is transformed into a highly beneficial one for both citizens and societies.